Effectiveness of Low Glycemic Index Diet Consultations Through a Diet Glycemic Assessment App Tool on Maternal and Neonatal Insulin Resistance: A Randomized Controlled Trial - Zhang, Yi; Wang, Liping; Yang, Wenhong; Niu, Dayan; Li, Chunying; Wang, Liling; Gu, Ping; Xia, Yingqian; Shen, Ying; Yan, Juhua; Zhao, Qian; Mu, Kai; et al. (JMIR Publications, 2019)
BackgroundLow glycemic index (LGI) diet has shown to be effective in reducing maternal and neonatal complications in high-risk pregnancies. ObjectiveThis trial aimed to examine the effectiveness of individualized LGI diet consultations based on the accurate diet glycemic load (GL) assessment tool on maternal and neonatal insulin resistance levels and diet behavior changes in overweight and obese pregnant women. MethodsOverweight and obese pregnant women were recruited before 16 weeks of gestation and randomized to the LGI diet arm or the control arm. All participants received standard dietary education according to the Chinese Dietary Guide for Pregnant Women. In the intervention arm, additional individualized dietary GL assessments were performed using an app and instructions of lowering diet glycemic index (GI) to achieve LGI diet were provided by a clinical dietitian at early, middle, and late gestation. Primary outcomes were serum insulin at late gestation, incidence of gestational diabetes mellitus (GDM) for mothers, and cord blood C-peptide level of neonates. ResultsIn total, 400 subjects were randomized and received different interventions. There were no significant differences in maternal serum insulin levels (13.2 [9.3−13.2] uU/mL vs 12.4 [10.5−12.4] uU/mL), incidence of GDM (45 [22.5%] vs 43 [21.5%]), or cord blood C-peptide levels (mean 0.9ng/mL [SD 0.7] vs mean 0.8ng/mL [SD 0.6]) in the intervention group compared with the controls. The diet GI at late gestation was similar (mean 63.2 [SD 10.4] vs mean 64.3 [SD 10.4]), whereas greater diet fiber intake was observed in the intervention group (mean 11.6 grams [SD 8.0] vs mean 9.0 grams [SD 5.6]; P=.006). Adherence measurements did not significantly differ between 2 groups. ConclusionsIndividualized LGI diet consultations for overweight and obese pregnant women failed to make a significant difference in maternal or neonatal insulin resistance compared with the standard gestational diet consultation. Trial RegistrationClinicalTrials.gov NCT01628835; http://clinicaltrials.gov/ct2/show/NCT01628835 (Archived by WebCite at http://www.webcitation.org/77LHgWP0k)